Karaiyar: an etymological analysis - Srikanthan, S. (University of Jaffna, 2015)
Anthropology and linguistics are intertwined fields of study. The method of etymological analysis is useful to explore the cultural significance of a particular community in the complex world societies. It is to be emphasized that all diverse societies in the present world have not suddenly appeared; in contrast every society has gradually evolved by adapting their cultural customs and norms to their surrounding environments from time immemorial. In this context this study attempts to discuss the etymological roots of karaiyar, an indigenous fishing community inhabited on the Jaffna coastal area as a prominent fishing caste group and on the East coastal belt of Tamil Nadu State as a notable peculiar caste group based on three major approaches : geographical, occupational and ethno historical. The social identity of the karaiyar also evolved by their descent, genealogy, geographical distribution, etc., which were developed gradually during the course of their long history.